Structural Modeling of Djenkolic Acid with Sulfur Replaced by Selenium and Tellurium - Melnikov, Petr (Molecules, 2014)
The comparative structural modeling of djenkolic acid and its derivatives containing selenium and tellurium in chalcogen sites (Ch = Se, Te) has provided detailed information about the bond lengths and bond angles, filling the gap in what we know about the structural characteristics of these aminoacids. The investigation using the molecular mechanics technique with good approximation confirmed the available information on X-ray refinements for the related compounds methionine and selenomethionine, as well as for an estimate made earlier for telluromethionine. It was shown that the Ch-C(3) and Ch-C(4) bond lengths grow in parallel with the increasing anionic radii. Although the distances C-C, C-O, and C-N are very similar, the geometry of conformers is quite different owing to the possibility of rotation about four carbon atoms, hence the remarkable variability observed in dihedral angles. It was shown that the compounds contain a rigid block with two Ch atoms connected through a methylene group. The standard program Gaussian 03 with graphical interface Gaussview 4.1.2 has proved to be satisfactory tool for the structural description of less-common bioactive compositions when direct X-ray results are absent.